THU0040 Realtime Analysis of Monocyte Migration in 3D Synovial Micromass Tissue Cultures. (23rd January 2014) - Byrne, R.; von Dalwigk, K.; Hladik, A.; Steiner, G.; Smolen, J. S.; Kiener, H.; Scheinecker, C.
Abstract : Background: Monocytes (Mo) are among the first hematopoietic cells to migrate into the inflamed synovial tissue of arthritic joints. Monocyte migration appears to be associated with the expanding synovial lining network of fibroblast-like synovial cells (FLS). Whether cognitive interaction between Mo and FLS is required for an orchestrated migratory behavior has not been analyzed so far. Objectives: We analyzed Mo migratory activity under inflammatory conditions in regard to cell-cell interactions with FLS. Methods: Human FLS were prepared from synovial tissues obtained as discarded specimens following joint arthroplasty. CD14 + Mo were isolated from peripheral blood by magnetic bead sorting. FLS and Mo were labeled with fluorescent membrane dyes and cultured in spherical extracellular matrix micromasses with an average size of 1.5 mm for up to two weeks. For stimulation experiments, micromasses were cultured in medium containing 10 ng/ml of tumor necrosis factor (TNF). At different time-points cell migration was monitored in individual micromasses by real-time confocal microscopy. Results: Cell migration could be subdivided into three successive phases of cell movement. Phase I (day 1-3 of culture) was characterized by the formation of the synovial lining layer. Mo in close contact with FLS appeared sessile. On average 20% of Mo were in no apparent contact with FLS and displayed a mobile and seeking behavior. During phase II (day 3-7) already >95% of Mo were in contact with FLS. The majority of Mo remained sessile whereas a fraction of Mo displayed a directed cell movement with an impressive maximum speed of up to 15 mcm/min. In addition the formation of Mo cell clusters was observed. The rapid Mo migration finally ceased during phase III (day 7-14). The addition of TNF i) increased the frequency and size of Mo cell clusters during phase II two and ii) prolonged the mobility of Mo into phase III. Conclusions: The 3D synovial tissue culture system allows to monitor and analyzed subtle migration patterns of Mo in relation to the organized synovial lining architecture. Ongoing experiments address molecular mechanism(s) of Mo – FLS interaction in order to identify potential targets for future therapeutic intervention in arthritis. Disclosure of Interest: None Declared